2009
DOI: 10.1002/sia.3010
|View full text |Cite
|
Sign up to set email alerts
|

ToF‐SIMS characterisation of methane‐ and hydrogen‐plasma‐modified graphite using principal component analysis

Abstract: Time of flight secondary ion mass spectrometry (ToF-SIMS) has been used to determine the extent of surface modification of highly ordered pyrolytic graphite (HOPG) samples that were exposed to radio-frequency methane and hydrogen plasmas. The ToF-SIMS measurements were examined with the multivariate method of principal component analysis (PCA), to maximise the amount of spectral information retained in the analysis. This revealed that the plasma (methane or hydrogen plasma) modified HOPG exhibited greater hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Similarly, Figure 3 e,f are ToF-SIMS 2D maps of hydrocarbon fragment peaks C 4 H 10 + m/z + 58.0604 and C 5 H 9 + m/z + 69.0462 from the graphite mixing and stamping WE surface. Identification of these fragments as graphite fragments has been reported previously [ 30 , 31 ]. Additional SIMS spectral plots show dominant counts of these two peaks in supporting information (SI) Figure S1b .…”
Section: Resultsmentioning
confidence: 58%
“…Similarly, Figure 3 e,f are ToF-SIMS 2D maps of hydrocarbon fragment peaks C 4 H 10 + m/z + 58.0604 and C 5 H 9 + m/z + 69.0462 from the graphite mixing and stamping WE surface. Identification of these fragments as graphite fragments has been reported previously [ 30 , 31 ]. Additional SIMS spectral plots show dominant counts of these two peaks in supporting information (SI) Figure S1b .…”
Section: Resultsmentioning
confidence: 58%
“…1(c) shows peak intensities extracted from the mean spectra (calculated from the 10 normalised spectra for each sample), for the peaks with dominant loadings as determined from the PCA results. We have previously shown that the C 2 H 3 + and C 3 H 3 + fragments are symptomatic of pristine graphite [6]. The yields of these fragments are observed to decrease as the plasma exposure time is increased, which shows the nature of the surface becomes less like HOPG.…”
Section: Exposure Timementioning
confidence: 90%
“…The details of the chamber have been described elsewhere [6]. High purity methane (99.95% from Linde) was added to the chamber using a motorised automatic pressure controller, with chamber pressure monitored by a Baratron capacitive pressure gauge.…”
Section: Plasma Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Chiba et al investigated the carbon cluster emission from graphite . Deslandes et al determined the effect of surface modification of HOPG . Detter et al examined the matrix effect of granulated graphite on the Ag and Cu complex emission …”
Section: Introductionmentioning
confidence: 99%